Pengaruh Motivasi Belajar Terhadap Konsentrasi Belajar Siswa - Rana Meiyanda; Mutiara Mahardika; Wahyu Ashabul Jannah; Revan Marhamah; Rio Pujangga; Muhammad Hafidz Hidayatullah (Universitas Majalengka, 2026)
This study aims to analyze the effect of learning motivation on students’ learning concentration. Learning motivation is one of the important factors that can influence students’ ability to focus during the learning process. This research employed a quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. Data were collected through questionnaires distributed to respondents and analyzed using SmartPLS software. The learning motivation variable was measured through several indicators related to students’ learning encouragement, while the learning concentration variable was measured through indicators of students’ focus and attention during the learning process. The results showed that learning motivation had a positive and significant effect on students’ learning concentration with a path coefficient value of 0.821, a t-statistics value of 18.819, and a p-values value of 0.000. In addition, the R-square value of 0.677 indicated that learning motivation was able to explain 67.7% of students’ learning concentration. The findings also demonstrated that all indicators met the validity and reliability requirements, indicating that the research model was appropriate for use. Therefore, learning motivation is an important factor in improving students’ learning concentration during the learning process. Schools and teachers are expected to enhance students’ learning motivation through engaging learning strategies and a conducive learning environment.